Shift Work, Social Support, and Work Motivation Among Terminal Employees: A Case Study of Gambut Barakat Terminal, South Kalimantan - Tiara, Norma; Rahmawati, Rini (Universitas Proklamasi 45, 2025)
This study examines how a shift work system affects employees’ work motivation, considering social support as a mediating mechanism. The research took place at Gambut Barakat Type A Terminal, South Kalimantan, a public service facility that operates continuously with rotating morning, afternoon, and night schedules. A quantitative, causal comparative design was employed, and all 35 shift employees were surveyed using standardized instruments for shift work and social support. Data were analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that the shift work system has a positive impact on work motivation (β = 0.536) and also enhances perceived social support (β = 0.763). Social support has a positive effect on motivation (β = 0.383) and partially mediates the relationship between shift work and motivation (β = 0.409). The model yields an R² of 0.744, indicating that 74.4% of the variance in motivation is explained by the combined effect of shift work and social support. These findings highlight the importance of transparent and well-managed rosters accompanied by a supportive interpersonal climate. In continuous public service operations, equitable scheduling, combined with peer and supervisory support, can enhance employee motivation and help sustain performance over time.